Eksplorasi Bibliometrik tentang Hubungan Kebijakan Fiskal dengan Stabilitas Makroekonomi - Judijanto, Loso; Harsono, Iwan; Fadliyanti, Luluk; Purwadinata, Subhan (Sanskara Akuntansi dan Keuangan, 2024)
This research explores the relationship between fiscal policy and macroeconomic stability through in-depth bibliometric analysis, utilizing articles from various academic databases. Focusing on Indonesia, this study identifies trends, patterns and empirical evidence showing the impact of various fiscal policy tools on key macroeconomic indicators such as GDP growth, inflation rates and unemployment rates. Through a methodology that includes data collection, processing, descriptive analysis, and visualization, this research provides insights into the effectiveness of fiscal policy in stabilizing the economy as well as its interaction with monetary policy. The results show that effective coordination between fiscal and monetary policies is crucial for macroeconomic stability, especially in the face of economic crises. From a bibliometric perspective, this analysis also reveals underexplored research areas that have potential for further investigation.